NAVIGATING UNCERTAINTY: PROMOTING INDONESIAN FAMILY BUSINESSES THROUGH TIKTOK AS A SOCIAL COMMERCE PLATFORM - Syahrivar, Jhanghiz; Rozy, Ryo Fadhlur; Chairy, Chairy (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Family businesses, especially those that fall under the small and medium-sized enterprise (SME) classification, play a crucial role in numerous countries worldwide by fostering regional growth, driving innovation, and creating employment opportunities, all of which positively impact the national economy. The rapid advancements in the digital era have enabled family business practitioners to leverage digital sophistication to expand their businesses amidst political and economic uncertainties. This study aims to understand the motivations behind Indonesian family businesses' choice of TikTok as a social commerce platform and to explore their online promotional strategies utilizing this platform. Employing a qualitative approach, the research delves into why and how family businesses in Indonesia utilize TikTok for their marketing efforts. The findings reveal several factors that make TikTok an advantageous platform for family businesses. Firstly, TikTok is recognized as the most popular social media platform in Indonesia, making it a highly effective tool for attracting potential customers. Secondly, despite the technical challenges associated with digital platforms, TikTok is perceived as user-friendly. Thirdly, TikTok provides unique features that distinguish it from other social media platforms. Fourthly, TikTok is regarded as a cost-effective means of business promotion. Lastly, TikTok enhances customer engagement. Additionally, this paper examines various online promotional strategies employed by local family businesses on TikTok. The study provides valuable managerial insights for family business practitioners.